The potential of an extract of Zingiber zerumbet (L.) Smith as a feed additive to improve the production performances and meat nutritional composition of broiler chickens - Rahayu, I D; Widodo, W; Prihartini, Indah; Winaya, Aris; Zalizar, Lili; Untari, Tri; Mel, Maizirwan (IOP Publishing, 2019)
This study aimed at replacing the use of antibiotic growth promoters (AGP) as the feed additive with the Zingiber zerumbet (L.) Smith extract (ZZE) to control Salmonellosis in broiler chickens. This study employed the completely randomized design (CRD), five treatments, namely: T0 (basal diet), T1 (basal diet + S. enteridis infection), T2 (basal diet + S. enteridis infection + 0.33 % ZZE), T3 (basal diet + S. enteridis infection + 0.67 % ZZE), and T4 (basal diet + S. enteridis infection + 1 % ZZE). The addition of the Z. zerumbet extract did not seem to affect the production performances, in which the average feed consumption was 69.38 g ± 4.43 g to 72.71 g ± 4.92 g, body weight gain was 35.67 g ± 1.40 g to 38.30 g ± 3.85 g, feed conversion was 1.89 ± 0.11 to 2.04 ± 0.11, final weight was 1 287.80 g ± 49.97 g up to 1 380.50 g ± 134.90 g, and percentage of carcass was 60.90 % to 68.48 %. However, the use of Z. zerumbet extract with the highest concentration at 1 % decreased the crude fat of meat.